Sharing studies between IMT-advanced (4G) and digital video broadcasting at 800MHZ band - Ng, Eng Hui (2010)
This thesis is generally about the study and simulation of the feasibility to coexist between the mobile service which is represented by the IMT-Advanced (4G) and broadcasting service which is represented by the Digital Video Broadcasting - Terrestrial (DVB-T) at 800MHz band. In this thesis, the specifications and standards of the 1MT-Advanced and the Digital Video Broadcasting -Terrestrial are studied and identified. Besides. SEAMCAT (Spectrum Engineering Advanced Monte- Carlo Analysis Tool) simulator is learnt and operated. SEAMCAT simulation is done on the coexistence of these two different services by determine the separation distance and frequency separation. The focus of this project is to find out the optimum frequency separation when the systems are coexisting at the same geographical location and the minimum separation distance when the systems are coexisting at the same operation frequency band. Consequently, the ideal separation distance and frequency separation are obtained. Lastly, the simulation results are taken into consideration to verify the feasibility to coexist between these two different services with the acceptable level of interference.